Formation of a quantitative system in China - Dossymbekova, R. O. (Journal of Oriental Studies, 2016)
This article reviews the history of numerology in ancient China. It considered detailed and separately the numbers 1 – 10, also provides defi nitions and examples. We give a general description of the history of numerology in China based on studies of scientists and thinkers. It makes history of Chinese numerology complemented by accurate and interesting information. Keywords: